"Notes Turn Into Angel Wings and Fly Upward": A Small Journal Kept During the COVID-19 Crisis, Phase One - Parker, William (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
William Parker is a bassist, improviser, composer, writer, and educator from New York City. In this journal, he reflects on the first year of the COVID-19 pandemic.